Speckle filtering techniques for different quality level of healthy kidney ultrasound images - Wan Kairuddin, Wan Nur Hafsh; Wan Mahmud, Wan Mahani Hafizah; Nazari, Ain (Penerbit Uthm, 2019)
The increasing reliance of modern medicine on diagnostic techniques such as computerized tomography, histopathology, magnetic resonance imaging, radiology and ultrasound imaging shows the importance of medical images [1]. Ultrasound (US) imaging is an imaging technique that is far the least expensive and most portable comparing to other standard medical imaging modalities. US imaging is a safe technique, easy to use, noninvasive nature and provides real time imaging, hence it is used extensively. But on the downside, ultrasound imaging has a poor resolution of image compared with other medical imaging instrument like Magnetic Resonance Imaging (MRI). US has wide spread application as a primary diagnostic aid of obstetrics and gynecology, due to the lack of ionizing radiation or strong magnetic fields. General US imaging applications include soft tissue organ and carotid artery